Perceptions of pregnant women about the role of partners in prenatal consultations - Iarlla Silva Ferreira; Ana Fátima Carvalho Fernandes; Karísia Karen Ricarte Lô; Thaissa Pinto de Melo; Altamira Mendoça Félix Gomes; Ivna Silva Andrade (Rev Rene)
Objective: to understand the perception of pregnant women about the role of partners in prenatal consultations. Methods: qualitative study with 15 pregnant women. Data was collected through non-participant observation and semi-structured interview, organized and analyzed based on Content Analysis technique. Results: the speeches were grouped into three categories: the presence of the father during the consultations as an adherence factor to prenatal care, the man’s participation in the care of the pregnant woman and the child, and the partner as a confidence promoter. Conclusion: women reported feelings of safety and increased confidence when accompanied by partners in the consultations.